2020
DOI: 10.12659/msm.926602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Associated with Anxiety and Depression in Chinese Visiting Scholars in the United States During the COVID-19 Pandemic Assessed by Online Questionnaires

Abstract: Background This study aimed to use online questionnaires to evaluate the factors associated with anxiety and depression in Chinese visiting scholars in the United States during the COVID-19 pandemic. Material/Methods Using a cross-sectional design, 311 Chinese scholars visiting 41 states in the United States were interviewed on 20 and 21 April 2020 through WeChat using the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 (GAD-7) questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
0
2
0
3
Order By: Relevance
“…In that sense, it becomes fundamental to understand which psychosocial factors may play a role in the prevention of these conditions and its burdensome consequences. Resilience, perceived social support ( Zhao et al, 2020 ; Tamura, 2021 ), perceived family support ( Su et al, 2017 ) and family communication skills ( Park et al, 2022 ) have been reported in the literature as important protective factors for symptoms of depression and for the adaptation to this life-threatening event. To optimize the prevention of these neuropsychiatric disorders, clinicians and researchers need to be attentive, screen and monitor affective symptoms in patients with cancer ( Walker et al, 2014 ) and, additionally, understand and bolster the psychosocial resources available both for patients and their relatives ( Seiler and Jenewein, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, it becomes fundamental to understand which psychosocial factors may play a role in the prevention of these conditions and its burdensome consequences. Resilience, perceived social support ( Zhao et al, 2020 ; Tamura, 2021 ), perceived family support ( Su et al, 2017 ) and family communication skills ( Park et al, 2022 ) have been reported in the literature as important protective factors for symptoms of depression and for the adaptation to this life-threatening event. To optimize the prevention of these neuropsychiatric disorders, clinicians and researchers need to be attentive, screen and monitor affective symptoms in patients with cancer ( Walker et al, 2014 ) and, additionally, understand and bolster the psychosocial resources available both for patients and their relatives ( Seiler and Jenewein, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The research shows that during the epidemic period of novel coronavirus pneumonia, Chinese students and scholars living in the United States experienced serious psychological distress. Among the 311 respondents, 69 (22.2%) reported no anxiety or depression symptoms, 63 (20.3%) reported that they were in a state of severe anxiety, and 67 (21.5%) reported that they were in a state of severe depression (Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hasta la actualidad, han informado que la carga económica, el apoyo familiar y la capital social afecta el estado de salud mental. El aislamiento social, incluida la exclusión social y el bajo capital social, también conduce a problemas psicológicos que son inducidos por la COVID-19 (12) .…”
Section: Introductionunclassified